NEEDS AND DETERMINANTS OF ACCESS TO CLIMATE INFORMATION SERVICES BY WOMEN PRODUCERS IN SENEGAL - Diouf Seynabou; Ouédraogo, Issa; Zougmoré, Robert B.; Ouédraogo, Mathieu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Climate change affects differently men and women around the world. Due to women’s limited access to, and control over key assets, information and inputs for instance, they tend to be disadvantaged in terms of ability, flexibility and means to change their agricultural practices to adapt to a changing climate (Bryan et al. 2012). In sub-Saharan Africa in particular, where women are mostly engaged in rain-fed agriculture under precarious conditions, the effects of land degradation linked to climate change are increasingly affecting their production system. This is why the gender roles in climate-related practices and policies is more and more desired. In order to improve farmers’ capacity to cope with recurrent climate variability through the use of climate information, a study was conducted in 10 Regions of Senegal. The specific objectives were to: i) understand and identify farming adaptation practices used by men and women, ii) determine the climate information needs from women, and iii) identify the factors that can influence women's access to climate information.